Varieties developed for medicinal crops - Bindu, K Hima (Indian Horticulture, 2023)
Increased demand for natural products is creating a high pressure on medicinal plants and natural resources, causing their severe depletion due to overexploitation and unsustainable collection practices. Improved varieties and methods for safe herbal raw material production help in bringing herbs under cultivation. ICAR-IIHR developed elite varieties of Aswagandha, Centella asiatica and Velvet bean. Technologies for safe production which can be adapted for medicinal crops are also available. The information on the available technologies for medicinal crop production at ICAR-IIHR are discussed here in this article.